Free-Space Laser Communications XXXV 2023
DOI: 10.1117/12.2649591
|View full text |Cite
|
Sign up to set email alerts
|

A transmitter and receiver for lunar communications on the ANU Optical Ground Station

Abstract: The Australian National University (ANU) Optical Communications Ground Station (OCGS) is currently under development at Mt. Stromlo Observatory in Canberra, Australia. The OCGS will be compatible with a range of wavelengths, coding schemes, and techniques to cover satellites in Low Earth Orbit to Lunar and deep-space, and provide a platform for quantum communication from satellites. We have conducted a feasibility study and preliminary design review for the development of an instrument to support the CCSDS hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Accounting for the lunar regolith’s effects in electromagnetic simulations is crucial as it has been observed that this lossy ground can significantly affect antenna performance, particularly at higher frequencies. The average permittivity of lunar soil was determined to be 3, as referenced in [ 80 , 81 , 82 , 83 ]. Within the lunar environment, the antenna demonstrated a gain of 2.3 dB across a bandwidth ranging from 2.3 GHz to 2.7 GHz.…”
Section: Lunar Antenna Typesmentioning
confidence: 99%
“…Accounting for the lunar regolith’s effects in electromagnetic simulations is crucial as it has been observed that this lossy ground can significantly affect antenna performance, particularly at higher frequencies. The average permittivity of lunar soil was determined to be 3, as referenced in [ 80 , 81 , 82 , 83 ]. Within the lunar environment, the antenna demonstrated a gain of 2.3 dB across a bandwidth ranging from 2.3 GHz to 2.7 GHz.…”
Section: Lunar Antenna Typesmentioning
confidence: 99%